Peningkatan Daya Saing UMKM Desa Lemah Abang Melalui Pembangunan Dan Manajemen Website - Gifthera Dwilestari; Edi Tohidi; Raena Agustin Laeliyah; Anita Nur Kirana; Hilya Ashfia Nabila (CV. Multi Kreasi Media, 2022)
This community service is an initiative that aims to overcome the challenges faced by Micro, Small and Medium Enterprises (MSMEs) in Lemahabang Village in facing the digital era[1]. In the midst of the rapid development of information technology, websites have become a crucial tool for MSMEs in developing their business. However, many MSMEs in rural areas such as Lemahabang Village still face obstacles in understanding and managing their websites. In this situation analysis, we will explain the location of the partners and the cases that occurred, the social and cultural conditions of Lemahabang Village, the special problems faced by MSMEs there, the methods or approaches used in the service, and the implications of the results of the service for the community. The results of the activity